NZVI-Al / biochar adsorbent as well as preparation method and application thereof
By loading nano zero-valent iron on biochar, an efficient nZVI@Al/biochar adsorbent was prepared, which solved the problem of insufficient adsorption performance of oleracin in the prior art, and achieved significantly improved adsorption volume and environmentally friendly Pollution control effect.
Patent Information
- Application Number
- CN202411507890.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-07
AI Technical Summary
In the prior art, when dealing with oleracin contamination, there are many limitations in biological treatment, chemical oxidation and photolysis. Although the adsorption method is effective, it lacks the adsorption performance of oleracin and lacks efficient adsorption materials.
Using nZVI@Al/biochar adsorbent, biochar is made by pyrolyzing rice straw powder and loading nano zero-valent iron (nZVI) on its surface to form Al/biochar precursor material, and then through liquid phase reduction method To improve dispersion stability, nZVI@Al/biochar adsorbent with high adsorption properties was prepared.
The maximum adsorption amount to oleracillin was significantly improved, and the improvement of 170.60 mg/g and 85.07 mg/g compared with the traditional method, which proved the excellent performance of nZVI@Al/biochar adsorbent in oleracillin pollution control, and It provides a new way to recycling rice straw, which has good environmental benefits.
Smart Images

Figure CN119258983A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmental functional materials and biomass resource utilization, and specifically relates to a nZVI@Al / biochar adsorbent and a preparation method and application thereof. Background Art
[0002] Oxytetracycline is a class of antibiotics widely used in veterinary and human medicine. They are widely used to prevent and treat a variety of bacterial infections. However, due to their widespread use, oxytetracycline antibiotics have been found to leave traces in the environment, including in soil, water and crops. Therefore, sufficient attention should be paid to the current status of oxytetracycline in the environment, its ecological risks and its risks to human health, and it is of great significance to find reasonable and effective methods to control its pollution.
[0003] At present, the treatment methods for oxytetracycline mainly include biological treatment, chemical oxidation, photolysis and adsorption. However, biological treatment is difficult to screen for specific bacteria, and the reaction process has high requirements for water quality; chemical oxidation requires a large amount of reagents and has high treatment costs; photolysis has high requirements for high-energy light sources and special reactors, and is greatly affected by lighting conditions and the environment. Adsorption has the characteristics of simple operation, good treatment effect and recyclable adsorbents, and is considered to be a very promising water treatment method.
[0004] Biochar is produced by pyrolysis of wood, straw and other organic materials. Biochar has a series of functional structures, such as oxygen-containing groups and pore structures, which can provide active sites for the reaction system. Due to its low cost and environmental friendliness, biochar is increasingly being used to resist biological degradation. Al(OH)3-modified biochar is a method of modifying biochar with aluminum hydroxide, which can increase the surface active sites of biochar and improve its adsorption capacity and selectivity for pollutants such as organic matter and heavy metal ions. Nano-zero-valent iron has been proven to be the most popular and promising nanomaterial for reducing water pollutants due to its high specific surface area, strong reactivity, standard redox potential and low cost.
[0005] However, there are few studies on the preparation of adsorption materials for oxytetracycline. Therefore, it is of great significance to invent an adsorption material with good adsorption effect on oxytetracycline. Summary of the invention
[0006] Purpose of the invention: The purpose of the present invention is to provide a nZVI@Al / biochar adsorbent and its preparation method and application in view of the deficiencies of the prior art. The nZVI@Al / biochar adsorbent prepared by the present invention exhibits excellent adsorption performance for oxytetracycline and can be used as a good adsorbent for oxytetracycline pollution control.
[0007] Technical solution: The purpose of the present invention is achieved through the following technical solution:
[0008] The present invention provides a method for preparing a nZVI@Al / biochar adsorbent, comprising the following steps:
[0009] (1) pyrolyzing rice straw powder under an inert atmosphere to obtain rice straw biochar;
[0010] (2) dissolving aluminum salt in water, stirring evenly, adding the rice straw biochar obtained in step (1), and stirring to obtain a mixed solution; then adding alkaline solution until the pH of the mixed solution is 5-10, continuing to stir for 0.5-1h, and post-treating to obtain an Al / biochar precursor material;
[0011] (3) adding the Al / biochar precursor material obtained in step (2) to iron salt, ethanol and water, and stirring until the solid is dissolved to obtain a mixed solution;
[0012] (4) Continue stirring under an inert atmosphere, add sodium borohydride solution to the mixed solution obtained in step (3), and continue stirring for 0.5-1h;
[0013] (5) After the reaction is completed, the precipitate is obtained by centrifugation, and the precipitate is washed and dried to finally obtain the nZVI@Al / biochar adsorbent.
[0014] The present invention prepares biochar from rice straw powder, and the biochar has a series of functional structures, such as oxygen-containing groups and pore structures, which can provide active sites for the reaction system. The dispersion stability can be improved by loading nZVI into the biochar using a liquid phase reduction method.
[0015] Preferably, in step (1), the rice straw powder is obtained by drying the rice straw to constant weight, sieving and then grinding; the drying temperature is 95-105° C., and the time is 2-2.5 h; and the mesh size of the sieving is 80 mesh.
[0016] Preferably, in step (1), the inert atmosphere is N2 atmosphere.
[0017] Preferably, in step (1), the pyrolysis is carried out in a tubular furnace.
[0018] Preferably, in step (1), the pyrolysis condition is to increase the temperature to 500-700°C at a heating rate of 8-10°C / min and keep the temperature at this temperature for 2-2.5h.
[0019] Preferably, in step (2), the aluminum salt is aluminum sulfate 18hydrate, and the concentration of the aqueous solution of aluminum sulfate 18hydrate is 0.6-0.8 mol / L; the mass volume concentration of rice straw biochar in the mixed solution is 1.5-2.0 g / L; and the alkali solution is 3.0 mol / L NaOH solution.
[0020] Preferably, in step (3), the iron salt is ferrous sulfate heptahydrate, and the concentration of the aqueous solution of ferrous sulfate heptahydrate is 0.05 mol / L; the mass concentration of Al / biochar precursor material in the mixed solution is 2.0 g / L.
[0021] Preferably, in step (3), the volume ratio of water to ethanol is 1:1-3:1.
[0022] Preferably, in step (4), the concentration of the sodium borohydride solution is 2.0 mol / L; and the volume ratio of the aqueous solution of the iron salt, ethanol and the sodium borohydride solution is 15:5:2.
[0023] Preferably, in step (5), the drying temperature is 45-50° C. and the drying time is 10-12 h.
[0024] Preferably, in step (5), the drying is carried out in a vacuum drying oven.
[0025] The present invention also provides a nZVI@Al / biochar adsorbent prepared by the above preparation method.
[0026] The present invention also provides the use of the nZVI@Al / biochar adsorbent in degrading oxytetracycline. The nZVI@Al / biochar adsorbent can be used to adsorb oxytetracycline.
[0027] Beneficial effects:
[0028] (1) The maximum adsorption capacity of oxytetracycline by the nZVI@Al / biochar adsorbent prepared by the present invention is 208.92 mg / g, which is 170.60 mg / g higher than the maximum adsorption capacity of oxytetracycline by straw biochar of 38.32 mg / g. Compared with the maximum adsorption capacity of oxytetracycline by the prepared Al / biochar adsorbent of 123.85 mg / g, the adsorption capacity of oxytetracycline is increased by 85.07 mg / g. Therefore, compared with the prior art, the adsorption performance of the nZVI@Al / biochar adsorbent prepared by the present invention is significantly improved, and it has a good adsorption effect on oxytetracycline.
[0029] (2) Using rice straw as the raw material for biochar has developed a new application method for rice straw, provided new ideas for the recycling of rice straw, and has good environmental benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 TEM images, EDS element distribution maps and SEM maps of the rice straw biochar, Al / biochar precursor material and nZVI@Al / biochar adsorbent prepared in Example 1;
[0031] Figure 2 XRD patterns of the rice straw biochar, Al / biochar precursor material, and nZVI@Al / biochar adsorbent prepared in Example 1;
[0032] Figure 3 FTIR spectra of the rice straw biochar, Al / biochar precursor material, and nZVI@Al / biochar adsorbent prepared in Example 1;
[0033] Figure 4 The adsorption kinetics of oxytetracycline on rice straw biochar, Al / biochar precursor material, and nZVI@Al / biochar adsorbent prepared in Example 1.
[0034] Figure 5 This is a graph showing the adsorption capacity of oxytetracycline for rice straw biochar, Al / biochar precursor material, and nZVI@Al / biochar adsorbent prepared in Example 1. DETAILED DESCRIPTION
[0035] The technical solution of the present invention is described in detail below through specific embodiments, but the protection scope of the present invention is not limited to the embodiments.
[0036] The experimental methods in the following examples are conventional methods unless otherwise specified. The experimental materials used in the following examples are commercially available products unless otherwise specified.
[0037] The rice straw used in the experiment was collected from rice fields.
[0038] Example 1 Preparation of nZVI@Al / biochar adsorbent
[0039] (1) drying the rice straw in a drying oven to remove most of the moisture at 100° C. for 2 h, grinding the dried rice straw into powder by mechanical crushing, and passing through an 80-mesh sieve to obtain rice straw powder;
[0040] (2) pyrolyzing the rice straw powder obtained in step (1) in a tubular furnace under a N2 atmosphere at a N2 flow rate of 240 mL / min, heating the temperature to 600°C at a rate of 10°C / min, and keeping the temperature at this temperature for 2 h. After natural cooling in the furnace, rice straw biochar (RBC) was obtained, which was sealed for later use;
[0041] (3) Take 500 ml of 0.6 mol / L Al2(SO4)3·18H2O solution and add it to a conical flask. Then slowly add 1 g of rice straw biochar to the conical flask and shake it appropriately with a horizontal shaker to confirm that the biochar is completely soaked in the Al2(SO4)3·18H2O solution. Then, slowly add 3.0 mol / L NaOH solution to the conical flask and stir at 200 rpm until the pH of the reaction mixture reaches 10. Then continue to stir at 200 rpm in the shaker for 30 min. Take it out from the shaker. The resulting slurry mixture consists of Al(OH)3 and sodium salt. After filtering the slurry with a vacuum filter, wash it with distilled water to remove the sodium salt, and then dry it in an oven at 80°C for 8 h to obtain Al / biochar precursor material (Al-BC).
[0042] (4) Transfer 0.4g of Al / biochar precursor material obtained in step (3) to a three-necked flask and add 150ml of 0.05mol / L FeSO4·7H2O aqueous solution and 50mL of ethanol, and stir evenly. Plug in a sealing stopper and pass N2 for one hour to expel the O2 dissolved in the bottle and water. Take 20ml of 2.0mol / L NaBH4 solution and pour it into a constant pressure funnel. Drip it into the three-necked flask at a rate of 1 drop / s. This process needs to be continued under a N2 atmosphere. Stir again for 30 minutes after dripping. Then wash it with deionized water and anhydrous ethanol, filter it, and dry it in a vacuum drying oven at 50°C for 12 hours to obtain nZVI@Al / biochar adsorbent.
[0043] The TEM images, EDS mapping patterns and SEM patterns of the rice straw biochar, Al / biochar precursor material and nZVI@Al / biochar prepared in this example are shown in Figure 1 .
[0044] From the SEM images, it can be seen that Figure 1 The original biochar surface in a has only a few cracks and wrinkles, and most of the surface is relatively smooth. Figure 1 b The surface of biochar Al / biochar precursor material is occupied by a dense layer of Al hydroxide, with particles attached to the surface, giving it a strong granular feel. Figure 1 c After loading nZVI, the surface of biochar has undergone a huge change, with more obvious large cracks and holes, and the surface has become rougher, with irregular wrinkles, exposing more internal structures, and there are also a large number of particles on the surface and inside, which may be FeO. Through a clearer TEM Figure 1 h. Figure 1 nTransmission electron microscopy scanning can be observed that the biochar after calcination contains solid granular iron compounds. Figure 1 (d~g), Figure 1In (im), EDS elemental analysis shows that the iron element is evenly distributed in the biochar, proving that Al, Fe 0 Successfully loaded on biochar.
[0045] The XRD patterns of the rice straw biochar, Al / biochar precursor material, and nZVI@Al / biochar prepared in this example are shown in Figure 2 . From the XRD spectrum, the peaks at 2θ of 43.72° and 64.28° indicate the presence of aluminum hydroxide. The weak peaks at 29.4°, 35.9°, 39.4°, 43.1°, 47.5°, and 48.5° are considered to be CaCO3 in the RBC and Al-BC structures. The CaCO3 peak on Al-BC is smaller than that on RBC, which indicates that Al(OH)3 helps in the removal of CaCO3. A strong peak appeared at 44.9° in nZVI@Al-BC, which is consistent with the α-Fe 0 There are weak diffraction peaks at 30.2°, 35.7° and 43.5°, indicating that there are a small amount of Fe2O3 and Fe3O4 in the material.
[0046] The FTIR images of the rice straw biochar, Al / biochar precursor material, and nZVI@Al / biochar prepared in this example are shown in Figure 3 From the FTIR spectrum, at 470cm -1 The XRD analysis shows that the Al-O is more likely. -1 The corresponding peak is the stretching vibration peak of the -OH group, indicating that the composite surface contains a large number of oxygen-containing functional groups. -1 The corresponding peak is the stretching vibration peak of the CH group. -1 and 1626cm -1 The corresponding peak is the stretching vibration peak of C=O and C=C double bonds. -1 and 801cm -1 The corresponding peaks are the bending vibration peaks of CO and CH, which may be caused by the benzene ring structure in aromatic compounds. -1 The broad peak at 400 nm corresponds to the vibration of Fe-O in Fe3O4. FTIR results show that the surface functional groups of nZVI@Al-BC increase significantly.
[0047] The method for investigating the adsorption performance of simulated pollutants provided by the present invention is as follows:
[0048] Adsorption test:
[0049] In order to study the adsorption kinetics, 0.2g of oxytetracycline (dried in an oven at 105°C for 2 hours) was weighed and placed in a 1000ml beaker, and pure water was added to dilute to the scale, and stirred to dissolve to prepare a 200mg / L oxytetracycline stock solution. 25mL of oxytetracycline stock solution and 75mL of pure water (initial concentration of 50mg / L) were measured, and 50mg of adsorbent was added and placed in a 100mL conical flask. The adsorption process was carried out at natural pH. Oscillating at a frequency of 150rpm at a temperature of 25°C, 1mL of solution was taken out at 5, 10, 15, 20, 25, 30, 40, 50 and 60min, and immediately filtered with a 0.45um filter membrane after taking out, and then the oxytetracycline concentration was determined by a UV spectrophotometer. All experiments were carried out in parallel 3 times, and blank controls were performed simultaneously.
[0050] When performing concentration measurements using a UV spectrophotometer, the Beer-Lambert law is applied to calculate the concentration of the sample.
[0051] The Beer-Lambert law formula is as follows:
[0052] A=ε · C · l
[0053] in,
[0054] A: absorbance (dimensionless)
[0055] ε: Molar absorptivity (L·mol-1·cm-1), which indicates the absorptivity of a solute at a specific wavelength
[0056] C: concentration (mol / L or g / L), concentration of solute
[0057] l: Optical path length (cm), usually the thickness of the cuvette.
[0058] Mathematical model of adsorption kinetics
[0059] The expression of pseudo-first-order kinetics is:
[0060] ln(q e -q t )=lnq e -k1t
[0061] The expression of pseudo-second-order kinetics is:
[0062]
[0063] Where: q t —Unit adsorption capacity at time t (mg / g);
[0064] q e —Unit adsorption capacity at equilibrium (mg / g);
[0065] Figure 4 The adsorption kinetics of oxytetracycline by rice straw biochar, Al / biochar precursor material, and nZVI@Al / biochar adsorbent prepared in Example 1 are shown in FIG. Figure 4 As shown, the first 10 minutes is the rapid adsorption stage, the material adsorbs rapidly, achieves a very high adsorption efficiency, and completes more than 90% of the adsorption of oxytetracycline. At the beginning of adsorption, the surface adsorption sites, the number of active functional groups, etc. are very sufficient, and the adsorption effect of oxytetracycline is excellent; as the adsorption reaction proceeds, the surface adsorption sites of the material are gradually occupied, and the adsorption of oxytetracycline begins to depend on the internal sites, and the adsorption rate begins to slow down; at 30 minutes, the adsorbent surface and internal sites are filled with oxytetracycline, and adsorption equilibrium is reached, the adsorption rate remains unchanged, and the adsorption effect of nZVI@Al / biochar adsorbent is the best. Example 1 is more in line with pseudo-first-order kinetics, indicating that physical adsorption accounts for a larger proportion of the oxytetracycline adsorption process. As can be seen from the figure, the adsorption capacity after modification is greatly improved.
[0066] Figure 5 The adsorption capacity of rice straw biochar, Al / biochar precursor material, and nZVI@Al / biochar adsorbent for oxytetracycline prepared in Example 1 is shown in FIG. Figure 5 As shown, the maximum adsorption capacity of rice straw biochar for oxytetracycline after 1440 minutes is 38.32 mg / g, while the maximum adsorption capacity of Al / biochar precursor material after 1440 minutes is 123.85 mg / g, and the maximum adsorption capacity of nZVI@Al / biochar adsorbent after 1440 minutes is 208.92 mg / g. Therefore, compared with rice straw biochar and Al / biochar precursor material, the nZVI@Al / biochar adsorbent prepared by the present invention has significantly improved adsorption performance and has a good adsorption effect on oxytetracycline.
[0067] Example 2
[0068] Referring to the preparation method of Example 1, the amount of aluminum sulfate 18hydrate added in step (2) of Example 1 was modified differently, so that the concentration of the aqueous solution of aluminum sulfate 18hydrate was 0.6 mol / L, 0.7 mol / L and 0.8 mol / L. In order to explore the effect of different aluminum salt concentrations on the adsorption of oxytetracycline by nZVI@Al / biochar materials, the other conditions were the same as in Example 1. The adsorption experiment of oxytetracycline was carried out according to the method and conditions described in Example 1, and the maximum adsorption amount is shown in Table 1.
[0069] Table 1 Adsorption data
[0070]
[0071] Example 3
[0072] Referring to the preparation method of Example 1, the amount of NaOH added in step (3) of Example 1 was modified to make the pH value of the reaction mixture 5, 8 and 10. In order to explore the effect of the pH of the reaction mixture on the adsorption of oxytetracycline by nZVI@Al / biochar materials, the other conditions were the same as those in Example 1. The adsorption experiment of oxytetracycline was carried out according to the method and conditions described in Example 1, and the maximum adsorption amount is shown in Table 2.
[0073] Table 2 Adsorption data
[0074]
[0075] Example 4
[0076] Referring to the preparation method of Example 1, the ratio of ethanol to water in step (4) of Example 1 was modified differently, and the volume ratio of ethanol to water was 1:1, 1:2, and 1:3. The effect of different ratios on the adsorption of oxytetracycline by nZVI@Al / biochar materials was explored, and the other conditions were the same as those in Example 1. The adsorption experiment of oxytetracycline was carried out according to the method and conditions described in Example 1, and the maximum adsorption amount is shown in Table 3.
[0077] Table 3 Adsorption data
[0078]
[0079] The adsorbent prepared by the method of the present invention has a good adsorption effect on oxytetracycline. In addition, it can be seen from Table 1, Table 2 and Table 3 that the adsorbents prepared under different conditions are subjected to oxytetracycline adsorption experiments, and the resulting adsorption capacities are different. Therefore, it is particularly important to select suitable materials for the adsorption of oxytetracycline.
[0080] As described above, although the present invention has been shown and described with reference to specific preferred embodiments, it should not be construed as limiting the present invention itself. Various changes in form and details may be made without departing from the spirit and scope of the present invention as defined in the appended claims.
Claims
1. A method for preparing a nZVI@Al / biochar adsorbent, characterized in that: The following steps are involved: (1) pyrolyzing rice straw powder under an inert atmosphere to obtain rice straw biochar; (2) dissolving aluminum salt in water, stirring evenly, adding the rice straw biochar obtained in step (1), and stirring to obtain a mixed solution; then adding alkaline solution until the pH of the mixed solution is 5-10, continuing to stir for 0.5-1h, and post-treating to obtain an Al / biochar precursor material; (3) adding the Al / biochar precursor material obtained in step (2) to iron salt, ethanol and water, and stirring until the solid is dissolved to obtain a mixed solution; (4) Continue stirring under an inert atmosphere, add sodium borohydride solution to the mixed solution obtained in step (3), and continue stirring for 0.5-1h; (5) After the reaction is completed, the precipitate is obtained by centrifugation, and the precipitate is washed and dried to finally obtain the nZVI@Al / biochar adsorbent.
2. The preparation method according to claim 1, characterized in that: In step (1), the rice straw powder is obtained by drying the rice straw to a constant weight, sieving and then grinding; the drying temperature is 95-105° C., and the time is 2-2.5 h; and the mesh size of the sieving is 80 meshes.
3. The preparation method according to claim 1, characterized in that: In step (1), the pyrolysis conditions are to increase the temperature to 500-700°C at a heating rate of 8-10°C / min and keep the temperature at this temperature for 2-2.5h.
4. The preparation method according to claim 1, characterized in that: In step (2), the aluminum salt is aluminum sulfate 18hydrate, and the concentration of the aqueous solution of aluminum sulfate 18hydrate is 0.6-0.8 mol / L; the mass volume concentration of rice straw biochar in the mixed solution is 1.5-2.0 g / L; and the alkali solution is 3.0 mol / L NaOH solution.
5. The preparation method according to claim 1, characterized in that: In step (3), the iron salt is ferrous sulfate heptahydrate, and the concentration of the aqueous solution of ferrous sulfate heptahydrate is 0.05 mol / L; the mass concentration of Al / biochar precursor material in the mixed solution is 2.0 g / L.
6. The preparation method according to claim 1, characterized in that: In step (3), the volume ratio of water to ethanol is 1:1-3:
1.
7. The preparation method according to claim 1, characterized in that: In step (4), the concentration of the sodium borohydride solution is 2.0 mol / L; the volume ratio of the aqueous solution of the iron salt, ethanol and the sodium borohydride solution is 15:5:
2.
8. The preparation method according to claim 1, characterized in that: In step (5), the drying temperature is 45-50°C and the drying time is 10-12h.
9. A nZVI@Al / biochar adsorbent prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the nZVI@Al / biochar adsorbent according to claim 9 in the degradation of oxytetracycline.
Citation Information
Cited By
Al-nZVI catalyst as well as preparation method and application thereof
CN122538126A